Cognition, Meaning and Kinship: Connectionist Models of Cultural Representation - H. McKellin, William (Culture, 1995)
Traditional anthropological models of kinship employ rule-based classical semantics to account for the meanings of kinship, clanship and the attribution of kin terms. This article uses cognitively-based, prototype semantics and distributed, sub-symbolic representations to explore the meanings of kinship relations among the Managalase of Papua New Guinea.